2020
DOI: 10.3390/f11101074
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Climate Variations on the Structure of Ground Beetle (Coleoptera: Carabidae) Assemblage in Forests and Wetlands

Abstract: We studied the effect of climate variations on the structure of the assemblage of ground beetles (Coleoptera: Carabidae) in a wetland and surrounding watershed forest. We analyzed the changes in the structure of the assemblage of ground beetles provoked by a two-year dry period against the background of studies carried out during the two-year wet period. Aridization influenced the structure of the assemblage of ground beetles more in wetlands than in forests. It was shown that despite the stabilizing effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…In soil arthropods were likely to have significant adaptations to the conditions of soil, humidity and tolerance to other soil management practices that may have enhanced their richness and abundance. Several studies have shown the elevated abundance of arthropods in the cultivated soil due to their adaptations and tolerance to the soil condition and tolerance to the tillage practices (Kirichenko-Babko et al, 2020;Sajjad et al, 2022). In this study, the species richness and abundance had a positive correlation with each other both in flood irrigated plots and drip irrigated plots.…”
Section: Discussionsupporting
confidence: 51%
“…In soil arthropods were likely to have significant adaptations to the conditions of soil, humidity and tolerance to other soil management practices that may have enhanced their richness and abundance. Several studies have shown the elevated abundance of arthropods in the cultivated soil due to their adaptations and tolerance to the soil condition and tolerance to the tillage practices (Kirichenko-Babko et al, 2020;Sajjad et al, 2022). In this study, the species richness and abundance had a positive correlation with each other both in flood irrigated plots and drip irrigated plots.…”
Section: Discussionsupporting
confidence: 51%
“…Objectives of such work must also include assessment of the forest canopy fauna since tropical canopies appear to be even more species rich than understory habitats (Erwin 1982;Charles and Basset 2005;Erwin et al 2005). Anthropogenic factors, particularly oil exploration and extraction and climate change are now driving broad changes to the fauna of these megadiverse areas (Finer et al 2009;Bass et al 2010;Kirichenko-Babko et al 2020). Thus, gaining increased understanding of rainforest insect assemblages like those at Yasuní is critical to assess and ameliorate the impacts, and to conserve the natural fauna of these unique habitats.…”
Section: Discussionmentioning
confidence: 99%
“…Arthropods play vital roles in ecological processes and are major components of highly diverse ecosystems ( Kim 1993 ; Samways 1993 ). With current rates of deforestation, forest degradation, and predicted changes associated with climate change such as aridization, many tropical forest species will disappear before they are described ( Kellert 1993 ; Kim 1993 ; Samways 1993 ; Godfray et al 1999 ; Dunn 2005 ; Finer et al 2008 ; Kim et al 2015 ; Kirichenko-Babko et al 2020 ; Wagner 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Preference for high humidities is not uncommon in epigean beetle species (Neve, 1994;Šustek et al, 2017;Kirichenko-Babko et al, 2020), and only a physiological comparison of D. kentuckensis and an epigean sister species could reveal if the lack of desiccation resistance is a cave adaptation and not an ancestral trait shared by other trechines. According to Maddison et al (2019), an epigean trechine beetle closely related to D. kentuckensis is the genus Trechus Clairville.…”
Section: Dehydration Resistancementioning
confidence: 99%